Concomitant proton pump inhibitor use does not reduce the efficacy of elbasvir/grazoprevir: A pooled analysis of 1, 322 patients with hepatitis C infection. Issue 8 (22nd August 2017) - Reau, Nancy; Robertson, Michael N.; Feng, Hwa‐Ping; Caro, Luzelena; Yeh, Wendy W.; Nguyen, Bach‐Yen T.; Wahl, Janice; Barr, Eliav; Hwang, Peggy; Klopfer, Stephanie O.
Abstract : Concomitant proton pump inhibitor (PPI) use reduces plasma concentrations of certain nonstructural protein 5A inhibitors, which are key components of modern hepatitis C infection (HCV) treatments. These reduced concentrations may decrease efficacy, leading to challenging treatment failures due to the development of resistance‐associated substitutions. This post‐hoc analysis assessed 12‐week sustained viral response (SVR12) and pharmacokinetics of fixed‐dose combination elbasvir/grazoprevir (EBR/GZR) in patients with HCV infection and self‐reported PPI use. Data were derived from six phase 3 EBR/GZR trials with treatment‐naive or treatment‐experienced genotype 1‐ or 4‐infected patients, with or without compensated cirrhosis. Baseline PPI use was defined as ≥7 consecutive days of use between study days –7 and 7. Bivariate analyses assessed PPI use and factors associated with SVR12 with sex, age (continuous and dichotomous), cirrhosis status, prior treatment status, baseline HCV RNA (continuous and dichotomous), HCV genotype, and baseline resistance‐associated substitutions as variables in the models. Overall, 12% (162/1, 322) of EBR/GZR‐treated patients reported baseline PPI use. Of those, 96% achieved SVR12. In patients without PPI use, 97% achieved SVR12. PPI use was not a predictive factor in achieving SVR12 based on a univariate analysis ( P = 0.188). In the bivariate models, none of the interaction terms involving PPI use were statistically significant. There was no significant effect of PPI usage, regardless of adjustment for considered factors. The estimated area under the curve and maximum concentration values for EBR were comparable among patients with and without reported PPI use. Conclusion : These results demonstrate that PPI use with EBR/GZR had no clinically significant effect on SVR12 rates in genotype 1/4‐infected patients with or without compensated cirrhosis. (clinicaltrials.gov identifiers: NCT02092350, NCT02105467, NCT02105662, NCT02105688, NCT02105701, NCT02358044) ( Hepatology Communications 2017;1:757–764)